Hemodiafiltration for children with stage 5 chronic kidney disease: technical aspects and outcomes - Ahlmann, Charlotte; Stronach, Lynsey; Waters, Kathryn; Walker, Kate; Oh, Jun; Schmitt, Claus P.; Ranchin, Bruno; Shroff, Rukshana (Pediatric nephrology, 2024)
Despite significant medical and technical improvements in the field of dialysis, the morbidity and mortality among patients with chronic kidney disease (CKD) stage 5 on dialysis remains extremely high. Hemodiafiltration (HDF), a dialysis method that combines the two main principles of hemodialysis (HD) and hemofiltration—diffusion and convection—has had a positive impact on survival when delivered with a high convective dose. Improved outcomes with HDF have been attributed to the following factors: HDF removes middle molecular weight uremic toxins including inflammatory cytokines, increases hemodynamic stability, and reduces inflammation and oxidative stress compared to conventional HD. Two randomized trials in adults have shown improved survival with HDF compared to high-flux HD. A large prospective cohort study in children has shown that HDF attenuated the progression of cardiovascular disease, improved bone turnover and growth, reduced inflammation, and improved blood pressure control compared to conventional HD. Importantly, children on HDF reported fewer headaches, dizziness, and cramps; had increased physical activity; and improved school attendance compared to those on HD. In this educational review, we discuss the technical aspects of HDF and results from pediatric studies, comparing outcomes on HDF vs. conventional HD. Convective volume, the cornerstone of treatment with HDF and a key determinant of outcomes in adult randomized trials, is discussed in detail, including the practical aspects of achieving an optimal convective volume.
Gesehen am 18.06.2024